Experimental Contribution Concerning the Effect of Carbonation Reaction on the Oxygen Permeability of Concrete - Belgacem, Mohamed El Ghazali; Talah, Aissa; Neves, Rui; Belhamel, Farid; Kechidi, Smail (Periodica Polytechnica Civil Engineering, 2020)
Reinforced concrete (RC) structures are prone to steel corrosion that affects their service life. The two main processes, involved in the destruction of the steel-concrete self-protection are the carbonation and the penetration of chlorides. Understanding the behavior of these degrading phenomena is of paramount importance to enhance the field of predicting the service life of RC structures. In this investigation, a total number of 54 cylindrical specimens (150×100 mm2) and 54 cubic specimens (100×100 mm2) from six different concrete mixtures covering a range of water-to-cement ratio (w/c) between 0.76 and 0.36 was tested. The effect of the carbonation reaction on the concrete oxygen permeability (assessed by a recent method), compressive strength, and weight has been investigated. The obtained data were analyzed to establish correlations to predict the oxygen permeability of non-carbonated concrete with concrete characteristics such as w/c ratio and compressive strength. Test results show good correlations. The results of the accelerated carbonation test showed that compressive strength increases with carbonation. Concerning the effect of carbonation reaction on concrete oxygen permeability which is the main goal of this paper, test results showed that carbonation considerably affects the concrete permeability. This result was observed for all concrete mixtures. Moreover, the relationship between carbonation depth and concrete oxygen permeability in ordinary concrete differed than high performance concrete. Furthermore, the increase of the oxygen permeability observed after the carbonation has been justified by the analysis of the Scanning Electron Microscopy images that show the formation of larger pores in comparison with non-carbonated concrete.